Analisis Pengaruh Customer Experience, Intensitas Periklanan Terhadap Minat Beli Gramedia.Com Dengan Brand Awareness Sebagai Variabel Intervening (Studi Pada Pelanggan Gramedia Semarang) - Masyhuri, Mardhi; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2016)
Gramedia bookstore is a company engaged in the retail industry by providing a network of bookstores across Indonesia..Â  Gramedia bookstore launches virtual store from his bookstore is Gramedia.com aims to expand the market share of the company. However Gramedia.com virtual store is having problems, is the low purchase intention on Gramedia.com. Seeing these problems, this study aims to analyze the effect of Customer Experience and Advertising Intensity against buying interest using Brand awareness as a mediator variable (intervening) study on customer Gramedia bookstore Semarang. This study used non probability sampling used for sampling. Data were collected from 117 respondents were selected using criteria of judgment that should have never made a purchase products Gramedia bookstore at any branch. Test method is a Maximum Likelihood analysis with AMOS program version 22.0. The result show that the customer experience and the advertising intensity of the positive effect buying interest, either through brand awareness as intervening nor affect directly. Then, brand awareness positive effect on consumer buying interest Semarang Gramedia bookstore to buy a book on the virtual store products Gramedia.com.